WEEDS : A POTENTIAL SOURCE FOR HUMAN WELFARE (International Journal of Food and Nutritional Sciences, 2022)
Weeds are unwanted plant grows in a place where some other plants are also growing or no other plant has to grow at all. Weeds are unwanted , harmful, dangerous or economically detrimental .Weeds are found common in both kharip and rabbi season [6]. Weed flora of Sangli district is very rich with family Asteraceae and Poaceae [9] . Weeds are native or non native plants that grow and reproduce aggressively [7]. Weeds are plants which do not have any specific requirement with respect to climatic conditions, nutrients ,space .They grow at disturbed and inhabited places. Weeds are useful to human beings as food,erosion control ,medicine ,aesthetic value, shelter, supply of organic matter and mineral nutrients to the soil [1].They posses a large number of medicinal properties which otherwise are not explored. These medicinal properties are by the virtue of their phytochemicals that they are used as therapeutic agents. Traditional healers recognized their medicinal potential and have utilized them for the treatment of human ailments .Weeds are also found to be resistant to most of the microbial diseases when compared to the cultivated crops [ 10] . Although some weeds have some beneficial impacts to man , his environment and livestock [ 2] .Weeds are an important source of medicines for indigenous people and have a highly significant over -representation in indigenous pharmacopoeias about other plants [ 2 ].Sometimes weeds can serve for both medicine and food ,while some serve as food because of their nutritional contents. The overlapping roles of wild plants as food and medicine have been discussed by various authors [2